FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN BERAS ORGANIK DI YOGYAKARTA - Munambar, Siwitri (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2019)
Quality food is one of the challenges that must be realized by the government. One of the quality foods is organic rice. Organic rice in addition to ensuring environmental sustainability is positive for consumer health. This research was conducted to determine the factors that influence consumer purchases of organic rice. The analytical method used in this research is factor analysis. Based on the results of data processing with explanatory factor analysis techniques, two factors are formed which influence consumer demand for organic rice in Yogyakarta. Factor I is product and factor II is consumer social.